Vibration attenuation control of ocean marine risers with axial-transverse couplings - Tung Lam Nguyen; Anh Duc Nguyen (Universitas Ahmad Dahlan, 2021)
The target of this paper is designing a boundary controller for vibration suppression of marine risers with coupling mechanisms under environmental loads. Based on energy approach and the equations of axial and transverse motions of the risers are derived. The Lyapunov direct method is employed to formulated the control placed at the riser top-end. Proof of existence and uniqueness of the solutions of the closed-loop system is provided. Stability analysis of the closed-loop system is also included.